Percutaneous debridement and washout of walled-off abdominal abscess and necrosis using flexible endoscopy: a large single-center experience - Mathers, Bradley; Moyer, Matthew; Mathew, Abraham; Dye, Charles; Levenick, John; Gusani, Niraj; Dougherty-Hamod, Brandy; McGarrity, Thomas (Endoscopy International Open, 2016)
Background and study aims: Direct percutaneous endoscopic necrosectomy has been described as a minimally invasive intervention for the debridement of walled-off pancreatic necrosis (WOPN). In this retrospective cohort study, we aimed to confirm these findings in a US referral center and evaluate the clinical value of this modality in the treatment of pancreatic necrosis as well as other types of intra-abdominal fluid collections and necrosis. Patients and methods: Twelve consecutive patients with WOPN or other abdominal abscess requiring debridement and washout underwent computed tomography (CT)-guided drainage catheter placement. Each patient then underwent direct percutaneous endoscopic necrosectomy and washout with repeat debridement performed until complete. Drains were then removed once output fell below 30 mL/day and imaging confirmed resolution. The primary endpoints were time to clinical resolution and sustained resolution at 1-year follow up. Results: Ten patients were treated for WOPN, one for necrotic hepatic abscesses, and one for omental necrosis. The median time to intervention was 85 days with an average of 2.3 necrosectomies performed. Complete removal of drains was accomplished in 11 patients (92 %). The median time to resolution was 57 days. No serious adverse events occurred; however, one patient developed pancreaticocutaneous fistulas. Ten patients completed 1-year surveillance of which none required drain replacement. No patients required surgery or repeat endoscopy.Conclusions: This series supports the premise that direct percutaneous endoscopic necrosectomy is a safe and effective intervention for intra-abdominal fluid collections and necrosis in appropriately selected patients. Our study demonstrates a high clinical success rate with minimal adverse events. This modality offers several potential advantages over surgical and transgastric approaches including use of improved accessibility, an excellent safety profile, and requirement for only deep or moderate sedation.